The future rice strategy for India - Mohanty, Samarendu; Chengappa, P. G.; Mruthyunjaya, 1947-; Ladha, J. K. (Jagdish Kumar), 1952-; Baruah, Sampriti; Kannan, Elumalai; Manjunatha, A. V.; ScienceDirect eBooks (London : Academic Press, an imprint of Elsevier, 2017)
The Future Rice Strategy for India presents forward-looking insights toward achieving sustainable development of the rice sector, ensuring future food and nutritional security. As a staple food for many in India, including the economically disadvantaged, there are many concerns that affect the development of rice sector. Facing issues from environmental demands to economic stagnation, access to food, food inflation, and the Food Security Act (demand - supply - distribution of rice) achieving sustainability in production and exports is an important and urgent challenge. Using case studies to illustrate existing and potential issues, challenges and solutions, The Future Rice Strategy for India presents key strategic options while considering the implicit consequences. In addition, the findings enrich the strategy and policy formulation considerations for the role of rice in the country. This multidisciplinary approach features the expertise of rice scientists covering different aspects of rice sector; from breeding to consumer preferences and markets and trade.
Impact of climate change on riceImpact of Climate Change on Rice Yield: Crop Simulation Models; Climate Change Impact on Rice: Estimates From Econometric Models; Conclusions; References; Further Reading; Chapter 5 -- Structural Transformation of the Indian Rice Sector; Introduction; Rice production performance; Trends in rice exportS; Diversification of rice-based cropping systemS; The changing economic role of rice; Rice demand and supply; Consumption of Rice; Demand Elasticity; Rice Demand by 2030; Supply of Rice; Future challenges for the rice sector; Natural Resource Scarcity
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Rice -- India; Rice -- Economic aspects -- India; Agricultural productivity -- India; Agriculture -- Economic aspects -- India; Climatic changes -- India; TECHNOLOGY & ENGINEERING / Agriculture / Agronomy / Crop Science; Agricultural productivity; Agriculture -- Economic aspects; Climatic changes; Rice; Rice -- Economic aspects; India; Electronic books